Chlorophyllin Bait Formulation and Exposure to Different Spectrum of Visible Light on the Reproduction of Infected/Uninfected Snail Lymnaea acuminata - Navneet Kumar; D. K. Singh; Vinay Kumar Singh (Scientifica)
Fasciolosis is a waterborne disease, caused by Fasciola species. Snail Lymnaea acuminata is an intermediate host of these flukes. Control of snail population is major tool in reducing the incidences. Variation in light intensity and wavelength caused significant changes in reproduction pattern of snails. Maximum fecundity was noted with bait containing carbohydrate (starch, 468 ± 0.10/20 snails) or amino acid (serine, 319 ± 0.29/20 snails) as attractant. Sublethal feeding of chlorophyllin bait with starch or serine attractant to infected and uninfected snails caused significant reduction in fecundity, hatchability, and survivability. These significant changes are observed in snails exposed to different spectral band of visible light and sunlight. Maximum fecundity of 536 ± 2.0 and minimum of 89.3 ± 0.4 were noted in snails not fed with bait and exposed to sunlight and red spectral band, respectively. There was complete arrest in the fecundity of infected and uninfected snails and no survivability of uninfected snails after 48 h feeding with bait containing chlorophyllin + attractant. Minimum hatchability (9.25 ± 0.5) was noted in red light exposed, chlorophyllin + starch fed infected snails and hatching period of bait fed snails was prolonged. Conclusively, chlorophyllin bait and red light reduce reproduction capacity in snails.